2016
DOI: 10.1016/j.ijporl.2015.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Use of symptoms and risk factors to predict acute otitis media in infants

Abstract: Objectives Infants and children with upper respiratory tract infection (URI) often have concurrent acute otitis media (AOM). Young infants have less specific symptoms than older children. The purpose of this study was to evaluate the usefulness of symptoms and other risk factors in predicting the presence of AOM in infants. Methods Healthy infants, age ≤ four weeks, were enrolled and followed prospectively for up to age one year. Infants were scheduled for a research visit when their parents noted the onset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 20 publications
2
9
0
Order By: Relevance
“…The criteria for an AOM diagnosis which determined recruitment to the WATCH trial was bulging of the tympanic membrane and/or ear pain (or irritability in children under 3 years). This accords with Australian guidelines and is congruent with the trend to de-emphasise symptoms in the diagnosis of AOM [ 1 , 12 , 21 ]. However debate continues and it is common for guidelines and research protocols to include recent onset of symptoms in the diagnosis of AOM [ 20 22 ].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The criteria for an AOM diagnosis which determined recruitment to the WATCH trial was bulging of the tympanic membrane and/or ear pain (or irritability in children under 3 years). This accords with Australian guidelines and is congruent with the trend to de-emphasise symptoms in the diagnosis of AOM [ 1 , 12 , 21 ]. However debate continues and it is common for guidelines and research protocols to include recent onset of symptoms in the diagnosis of AOM [ 20 22 ].…”
Section: Discussionsupporting
confidence: 82%
“…In a study of children younger than 12 months with upper respiratory tract infections, higher scores of parental-reported symptoms (fever, earache, poor feeding, restless sleep, and irritability) were statistically associated with the prediction of AOM. However, these symptoms were most predictive of AOM when combined with reports of cough, severe ear pain, and the AOM risk factor of day care attendance [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 52 , 53 , 56 Contrary to previously reported association of fever with bacterial AOM, our study found that fever is more commonly associated with OME than with t-AOM. 54 , 57 So, fever by itself, in a fully vaccinated child, even at the age less than 2 years, should not point toward a diagnosis of bacterial infection, and otoscopic findings should be used to diagnose AOM and guide the use of antibiotics. 58 , 59 …”
Section: Discussionmentioning
confidence: 99%
“…52,53,56 Contrary to previously reported association of fever with bacterial AOM, our study found that fever is more commonly associated with OME than with t-AOM. 54,57 So, fever by itself, in a fully vaccinated child, even at the age less than 2 years, should not point toward a diagnosis of bacterial infection, and otoscopic findings should be used to diagnose AOM and guide the use of antibiotics. 58,59 Majority of our patients with OM were treated with antibiotics, despite physicians' awareness about the evidenced-based AAP recommendations to restrict antibiotic use for the treatment of AOM.…”
Section: Discussionmentioning
confidence: 99%